2011
DOI: 10.1002/ppul.21460
|View full text |Cite
|
Sign up to set email alerts
|

Bronchoalveolar lavage versus bolus administration of lucinactant, a synthetic surfactant in meconium aspiration in newborn lambs

Abstract: This study was designed to study effects of lung lavage versus the classical bolus instillation with a peptide-based synthetic surfactant (lucinactant) in a model of Meconium Aspiration Syndrome (MAS). Eighteen newborn lambs received meconium and were randomized to: the experimental meconium installation (eMAS) group-lambs with eMAS kept on conventional mechanical ventilation (control); the SF-Bolus group-eMAS receiving a lucinactant bolus (30 mg/ml); or the D-SF-Lavage group-eMAS treated with dilute lucinacta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…Similar findings have been reported by our service using the same experimental model, but lower doses of this surfactant (bolus of 100 mg/kg) [19,20] , and in a recent lamb study using artificial surfactant (lucinactant, Surfaxin ® , 180 mg/kg) [15] . Other animal models and human studies have shown that bolus administration of surfactant is associated with variable and usually modest improvement.…”
Section: Controlsupporting
confidence: 87%
“…Similar findings have been reported by our service using the same experimental model, but lower doses of this surfactant (bolus of 100 mg/kg) [19,20] , and in a recent lamb study using artificial surfactant (lucinactant, Surfaxin ® , 180 mg/kg) [15] . Other animal models and human studies have shown that bolus administration of surfactant is associated with variable and usually modest improvement.…”
Section: Controlsupporting
confidence: 87%
“…Consequently, surfactant replacement is gaining popularity as a standard therapy for management for NRDS [36]. Surfaxin (lucinactant) is the classical bolus instillation with a synthetic peptide-based surfactant [37]. Curosurf, also known as poractant alfa, is an exogenous porcine derived lung surfactant that enhances the clearance of apoptotic neutrophils [38].…”
Section: Discussionmentioning
confidence: 99%
“…The OI was calculated as mean airway pressure (cm H 2 O) × FiO 2 / PaO 2 (mm Hg) × 100 (34). To assess pulmonary ventilation independent of ventilator settings, ventilatory efficiency index was calculated as 3,800/PIP -positive end-expiratory pressure (cm H 2 O) × respiratory frequency (cycles per min) × PaCO 2 (34).…”
Section: Measurementsmentioning
confidence: 99%